End user satisfaction level of safety elements in lowcost strata housing: case study at PPR Kota Bharu - Sukeri, Hafiz Khairul Helmi (2024)
This research focuses on safety elements that influenced the end-user satisfaction of low-cost housing in Kelantan, particularly the PPR low-cost flats in Kota Bharu. The authorities of PPR should give serious attention to the safety elements in order to improve the satisfaction level of the end-user of the low-cost housing. Neglecting the safety elements of the low-cost housing can influenced the satisfaction level of the regarding the safety of the occupants. The research objectives include determining the safety element that influenced the satisfaction level of end user of the low-cost strata housing of PPR Kota Bharu and to rank the most important elements that influenced the satisfaction level of the end-user of PPR Kelantan Quantitative data analysis was conducted using questionnaires and surveys to gather information. The findings from the literature review and the questionnaire responses confirmed that lighting elements contribute most to the satisfaction level of the end-user of the PPR Kota Bharu followed by the indoor air quality, services, defect in building, design and material. It is recommended that future research broaden the case study's scope beyond PPR Kota Bharu and concentrate on a particular aspect of safety elements in low strata housing. Researchers might have a more comprehensive understanding of safety elements from many contexts and dig more into the chosen elements, eventually producing more accurate and perceptive results